EFEKTIVITAS INTERVENSI GARAM IODIUM MELALUI RUMAH TANGGA TERHADAP PENURUNAN TGR PADA ANAK SEKOLAH - Basuki Budiman; Komari Komari; M. Saidin (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2004)
THE EFFECTIVITY OF IODIZED SALT INTERVENTION THROUGH HOUSEHOLDS TO THE TGR IN SCHOOL CHILDREN.Background: The program to control iodine deficiency disorders (IDD) in Indonesia has been  implemented for more than three decades. The total goiter rate (TGR) was decreased dramatically  from 28.2% in 1982 to 9.8% in 1998. However national survey of iodine deficiency disorders in 2003 found that TGR at national level did not decrease in the period of 1998 to 2003. The number of severe endemic area was decreased, but the number of mild endemic area was increased. This raises the question on the effectivity of the program. The finding can lead to the condusion that using high dose iodine capsule might very effective compared to iodized salts. This paper reports the effect of a three-months iodized salt intervention to the TGR in school children. Objectives: To study the effectivity of iodized salt intervention through households in reducing goiter by palpation to assess the size of the thyroid glands of the goiter in the school children. Methods: A number of 81 families of school children aged 7-12 years were supplied with 2400 grams of iodized salt contained 60 ppm for three months. The study was conducted in endemic iodine deficiency area in Kola Batu, East Java province. The goiter was measured by palpation, and iodine in the urine was analyzed using wet digestion method. The measurements were conducted before and after the intervention.Results: After three months intervention, the goiter rate was decreased by 64.8 percents. There was a significant elevation of iodine excretion in urine level, even in the subjects who had not decreased their goiter gland volume.Conclusions: The study found that the supplementation of iodized salt through the households was very effective in reducing the TGR in school children.